Ignatian based online learning: An alternative to maintain the ‘presence’ in the distance learning - Fitriati, Anna (D3 English Program Universitas Merdeka Malang, 2020)
The Covid-19 pandemic has urged the government to establish a new regulation related to the teaching and learning process in Indonesia. Based on the Joint Ministerial Decree on Learning Guidelines during the Covid-19 pandemic, academic units in the orange and red zones are prohibited from conducting face-to-face learning. This policy requires academic units to switch the approach used in the teaching and learning process, and distance learning is applied as an effort to maintain the educational services during this Covid-19 pandemic. An effective approach should be applied and good preparation must be done to ensure that the teaching and learning process can run smoothly and effectively. Considering this situation the writer is interested in conducting classroom action research on the implementation of Ignatian Based Online Learning, which is developed based on the experience of Ignatius Loyola, to maintain the ‘presence’ in distance learning. The writer believes that distance learning should be more than just sending online home paper packets to the students. The teaching and learning process should be interactive to maintain the connection and to help teachers and students feel part of a group. It is expected that by implementing Ignatian Based Online Learning, the teacher and the students can feel the presence of each other and can work together to reach the course objectives even though they are separated from each other.Keywords: Ignatian based online learning, distance learning, classroom action research DOI: 10.26905/enjourme.v5i2.5151